Efficacy, Practicality, and Safety of Inhaled Methoxyflurane in Elderly Patients with Acute Trauma Pain: Subgroup Analysis of a Randomized, Controlled, Multicenter, Open-Label Trial (MEDITA) - Serra S (Journal of Pain Research, 2020)
Sossio Serra,1 Antonio Voza,2 Germana Ruggiano,3 Andrea Fabbri,4 Elisabetta Bonafede,5 Antonella Sblendido,6 Amedeo Soldi,6 Alberto Farina6 On behalf of the MEDITA Study Group1Emergency Department, Maurizio Bufalini Hospital, Cesena, Italy; 2Emergency Department, IRCCS Humanitas Research Teaching Hospital, Rozzano, Milan, Italy; 3Emergency Medicine Department, Santa Maria Annunziata Hospital, Florence, Italy; 4Department of Emergency Medicine, Morgagni-Pierantoni Hospital, Forlì, Italy; 5YGHEA, CRO Division of Ecol Studio Bioikos S.r.l., Bologna, Italy; 6Medical Affairs Department, Mundipharma Pharmaceuticals Srl, Milan, ItalyCorrespondence: Alberto FarinaMedical Affairs Department, Mundipharma Pharmaceuticals Srl, Milan, ItalyTel +39 02 3182881Email alberto.farina@mundipharma.itPurpose: Acute trauma pain management in the elderly population is a challenge. Inhaled methoxyflurane represents a promising treatment option; however, data in the elderly population are limited.Patients and Methods: Subgroup, post hoc analysis including 69 patients aged ≥ 65 years from a randomized, active-controlled, open-label study in the emergency setting. Key inclusion criterion was moderate-to-severe pain (Numerical Rating Scale [NRS] score ≥ 4]) secondary to trauma in a single limb. Patients received inhaled methoxyflurane (3 mL) or standard analgesic treatment (SAT; IV paracetamol 1 g or ketoprofen 100 mg for moderate pain [NRS 4– 6] and IV morphine 0.1mg/kg for severe pain [NRS ≥ 7]). The primary endpoint was the overall change in visual analog scale (VAS) pain intensity from randomization to the next 3, 5, and 10 min. Secondary endpoints included time to onset of pain relief (TOPR), efficacy up to 30 min, judgment of operators and patients, and safety.Results: Pain reduction over time was similar in both groups. Median TOPR was shorter for methoxyflurane (9 min; 95% CI: 7.8, 10.2 min) than SAT (15 min; 95% CI: 10.2, 19.8 min). In terms of treatment satisfaction, patients and operators rated treatment efficacy and practicality, respectively, as “Excellent” or “Very good” 5.7 times and 3.4 times more frequently than SAT. A similar rate of adverse events (methoxyflurane: 6 events; SAT: 7 events) was recorded, all non-serious. No clinically significant changes in vital signs parameters were observed, and methoxyflurane did not result in cases of bradycardia or hypotension.Conclusion: In elderly patients with trauma pain, inhaled methoxyflurane shows similar pain relief and safety compared to SAT, offering advantages in terms of onset of effect and user’s satisfaction. Although this analysis presents some methodological limitations, it provides the first specific evidence of the use of inhaled methoxyflurane in the elderly population.Trial Registration: EudraCT number: 2017-001565-25; Clinicaltrials.gov identifier NCT03585374.Keywords: acute pain, trauma, elderly, analgesia, emergency department, methoxyflurane, prehospital